Review: Pemanfaatan Tanaman sebagai Fitoterapi pada Diabetes Mellitus - Dewi, Ni Luh Kade Arman Anita; Prameswari, Putu Nimas Diyah; Cahyaningsih, Erna; Megawati, Fitria; Agustini, Ni Putu Dewi; Juliadi, Debby (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Diabetes is a chronic disease that occurs due to high levels of sugar in the blood, this can occur when the pancreas does not produce enough insulin (a hormone that regulates blood sugar or glucose), or when the body cannot effectively use the insulin it produces. Management of DM patients can be carried out with non-pharmacological and pharmacological therapies. The method used in the journal review was to search for the keyword